2008
DOI: 10.1021/nl801607p
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Studies of Nanomagnet-Based Logic Architecture

Abstract: We report a simulation study on interacting ensembles of Co nanomagnets that can perform basic logic operations and propagate logic signals where the state variable is the magnetization direction. Dipole field coupling between individual nanomagnets drives the logic functionality of the ensemble, and coordinated arrangements of the nanomagnets allow for the logic signal to propagate in a predictable way. Problems with the integrity of the logic signal arising from instabilities in the constituent magnetization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
130
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 12 publications
3
130
0
1
Order By: Relevance
“…magnetic wires bearing spin waves [3][4][5][6][7] or domain walls, [8][9][10] or nanomagnet networks. [11][12][13][14][15][16] The devices using spin waves represent a prospective direction taking into account their intrinsic low-power character, two usable features for processing, i.e. the amplitude and phase 3 (the latter is frequency-and wavenumber-dependent) of spin waves, and many available intrinsic attributes specific to waves [17][18][19][20] such as interference.…”
Section: Introductionmentioning
confidence: 99%
“…magnetic wires bearing spin waves [3][4][5][6][7] or domain walls, [8][9][10] or nanomagnet networks. [11][12][13][14][15][16] The devices using spin waves represent a prospective direction taking into account their intrinsic low-power character, two usable features for processing, i.e. the amplitude and phase 3 (the latter is frequency-and wavenumber-dependent) of spin waves, and many available intrinsic attributes specific to waves [17][18][19][20] such as interference.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] The nonvolatility of this technology, [ 1 ] its potential ultra-low power consumption, [ 4 ] the possibility to address data using spin-transfer-torque [ 5 ] or the spin-Hall effect, [ 6 ] the robustness of some designs against data transfer errors caused by thermal fl uctuations, [ 7 ] and the high speeds of data transfer [ 8 ] have identifi ed NML as a promising candidate for future computing technologies. One of the main unresolved challenges for NMLbased technology is data transfer in the vertical direction, a necessary step toward 3D spintronic systems.…”
Section: Doi: 101002/admi201600097mentioning
confidence: 99%
“…It has previously been shown that when grown on STO(110) substrates, a stress-based uniaxial anisotropy is induced in LSMO films whilst a biaxial anisotropy is observed for LSMO grown on (001)-oriented STO substrates. It has been shown that the addition of a biaxial anisotropy to interacting Co nanoislands enhances their hard axis stability [6] and consequently may be exploited in magnetic logic circuits. Here, we focus on the magnetic behaviour of LSMO films on (110)-oriented STO substrates and use micromagnetic simulations to show that by combining the shape anisotropy with a uniaxial anisotropy, it is possible to tailor the magnetic domain structure and ultimately the domain wall width.…”
Section: Introductionmentioning
confidence: 99%